2022
DOI: 10.29413/abs.2022-7.3.16
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effect of polyamines and indole on expression of stress adaptation genes in <i> Escherichia coli </i>

Abstract: Background. Indole and polyamines are involved in the regulation of physiological processes in bacteria associated with adaptation to stress, biofilm formation, antibiotic tolerance, and bacterial persistence. However, the molecular targets and mechanisms of action of these metabolites are still poorly understood. In this work, we studied the effect of polyamines and indole on the expression of such genes as: rpoS, relA, and spoT, encoding regulators of the general stress responses and starvation; hns and stpA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…Putrescine, cadaverine, and spermidine hydrochlorides (Sigma) were added to the medium for 2 h of cultivation at the concentrations indicated in the figures. Tryptophan (AppliChem) at 2 mM was added as previously described (Khaova et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Putrescine, cadaverine, and spermidine hydrochlorides (Sigma) were added to the medium for 2 h of cultivation at the concentrations indicated in the figures. Tryptophan (AppliChem) at 2 mM was added as previously described (Khaova et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Genes, the expression of which is upregulated by polyamines at the translational level, form the polyamine modulon (Igarashi, Kashiwagi, 2006. At the same time, there are data indicating that the regulatory activity of both polyamines and indole can be displayed on different levels of gene expression (Miller-Fleming et al, 2015;Lang et al, 2021;Khaova et al, 2022). Signaling molecules are able to form the regulatory networks that can form responses to various stresses (Tkachenko, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Being induced by indole, RaiA is involved in a persister cell formation [4]. Previously, we showed that, in addition to indole, polyamines are able to stimulate the raiA expression on the transcriptional level [5]. These metabolites have many different effects on cellular processes [6], including those carrying out through the modulation of gene expression [7].…”
Section: Introductionmentioning
confidence: 99%